Description of two new cicada species of the genus Poviliana Boulard (Insecta: Hemiptera, Cicadoidea, Cicadidae) from New Caledonia - Delorme, Quentin; Jourdan, Hervé; Mille, Christian (Zootaxa, 2015)
Poviliana dayubiikii Delorme sp. nov. and Poviliana montrouzieri Delorme sp. nov. are described from New Caledonia. They are respectively found in mid altitude rain forest on Mont Panié (570 m) and Col des Roussettes (300 m). Male calling songs of the two new species are described from the field recordings. A key to the species of Poviliana is also provided.